2009
DOI: 10.1111/j.1432-2277.2008.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of independent microarray datasets of renal biopsies identifies a robust transcript signature of acute allograft rejection

Abstract: Summary Transcriptomics could contribute significantly to the early and specific diagnosis of rejection episodes by defining ‘molecular Banff’ signatures. Recently, the description of pathogenesis‐based transcript sets offered a new opportunity for objective and quantitative diagnosis. Generating high‐quality transcript panels is thus critical to define high‐performance diagnostic classifier. In this study, a comparative analysis was performed across four different microarray datasets of heterogeneous sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 18 publications
3
82
0
1
Order By: Relevance
“…Second, we found that IFϩi was associated with upregulation of immune/ inflammatory pathways linked with acute cellular rejection. [17][18][19][20][21][22][23] The results lend credence to the view that early surveillance histology with or without targeted molecular analysis provides important prognostic information. 10,24 They also suggest that analysis of intragraft innate and adaptive immune pathways during early posttransplantation years 25 may provide the basis for interventions to subvert chronic deterioration in a subset of recipients with clinical expectations of excellent long-term outcome.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Second, we found that IFϩi was associated with upregulation of immune/ inflammatory pathways linked with acute cellular rejection. [17][18][19][20][21][22][23] The results lend credence to the view that early surveillance histology with or without targeted molecular analysis provides important prognostic information. 10,24 They also suggest that analysis of intragraft innate and adaptive immune pathways during early posttransplantation years 25 may provide the basis for interventions to subvert chronic deterioration in a subset of recipients with clinical expectations of excellent long-term outcome.…”
mentioning
confidence: 53%
“…22,23 Most striking, gene expression signatures associated with cytotoxic T lymphocytes, IFN-␥ response, B cells, and acute rejection were heavily enriched in IFϩi compared with normal and IF-alone groups (Supplemental Tables S2 and S3). Microarrays were also carried out on T4 biopsies from the three groups and were compared in a paired manner with the results of T12 microarrays to determine expression changes over time of acute rejection-associated genes.…”
Section: Ihc Targeted Molecular Profiling and Microarray Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…While many investigators have analyzed molecular changes in biopsies with histologic rejection, using either RT-PCR (17,18) or microarrays (19)(20)(21), these studies failed to distinguish TCMR from antibody-mediated rejection (ABMR), in part because the criteria for diagnosing ABMR, particularly C4d-negative ABMR, are evolving and remain controversial (22,23). Because of this, we established the Alberta Transplant Applied Genomics Centre (ATAGC) Reference Standard histology system (http://atagc.med.ualberta.ca/) in a prospective cohort of 403 indication biopsies (the BFC403 cohort).…”
Section: Introductionmentioning
confidence: 99%
“…Nephrology researchers have begun to employ these innovative high-throughput procedures to identify the whole basal expression profile of normal or pathological human kidney [100], to select biomarkers predicting acute and chronic allograft outcomes [101,102] and to assess more clearly the intricate molecular pathways associated to the pathogenesis and onset of several immunological renal diseases [103,104]. On the contrary, only few reports to date have been published describing the multi-genetic influence on drug response in nephrology.…”
Section: Pharmacogenomics and Immunosuppressive Drugs Used In Clinicamentioning
confidence: 99%